A Pilgrimage Through the Mist of Legends: Reconstructing the Life and Works of ‘Abd Al-Qadir Al-Jilani - Achmad Munjid (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2014)
Western scholars on Sufism so far have paid more attention to Sufi figures that left us with many written works, either in the form of poems, biography, apologia, or mystical treatise. Practically, al-Jilani only left us with three original works, wherein we do not find any ‘brilliant theory’ about Sufism. So, at the face value, this Western academic indifference about al-Jilani is just plainly plausible. Al-Jilani’s marginal position in the Western academic studies on Sufism in fact is an indication of a subtler ideological bias among many scholars. This article examines the life and works of al-Jilani while proposing a new theoretical basis in the study of Sufism. The writer argues that al-Jilani’s teaching is popular Sufism by definition Keywords: al-Jilani, spirituality, popular sufism